Penatalaksanaan Terapi Latihan pada Kasus Fraktur 1/3 Distal Humeri Dextra Post Orif (Open Reduction Internal Fixation) di RST DR. Soedjono - Nisaa, Fathrun; , Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: The fracture of 1/3 distal humeri is bone fracture occurring in right part of humeri bone located in 1/3 throw part of bone. The fracture is a trauma causing pain, limited range of joint movement, edema and limitation of functional ability of right arm. Purpose: To know physiotherapeutic administration in relieving pain, enhancing range of movement, reducing edema, and restoring elbow function in the case of 1/3 distal humeri dextra fracture by using modality of exercise therapy. Results: After 6 times therapy, it was found that painfull silence (T1: 2 turned into T6: 1), motion pain (T1: 6 turned into T6: 2), pressure pain (T1: 4 turned into T6: 2); enhancement range of active elbow joint movement (T1 S: 5-0-70 turned into S: 0-0-145), range of passive elbow joint movement (T1 S: 5-0-85 turned into S: 0-0-145), reduction of right edema (T1 : 20 turned into T6: 19), reduction of left edema (T1: 19 turned into T6: 19). Conclusion: Exercise therapy can relieve pain, improve range of movement, reduce edema and enhance functional of elbow.